(untitled) (Vallis Aurea, 2016)
The potential for diversification in segment of wine promotion is greatly wide. But it is important to empathize that supply market achieves almost perfect offer effect and competition, bought form domestic and foreign producers is great, so promotion efforts are one of the most important activities that producers have to make in order to make their market share satisfactory. Since wine is product that is described with large number of classification, suppliers have a wide range of promotional options. However, due to the great competition it is important to make every effort to gain as much of the buyers focus as possible.